Asuhan Kesehatan Gigi dan Mulut Pada Klien TN. A (19 THN) Dengan Kasus Karang Gigi - Mahardika, M. Ryza; Heriyanto , Yonan; Restuning, Sekar (Poltekkes Kemenkes Bandung, 2024)
Dental and oral diseases are not uncommon among people. This happens because of people's bad opinions and behavior regarding dental and oral health. A complaint that is often experienced by people is calculus. Calculus is a crusty substance that sticks to teeth, making them feel hard, yellow, and possibly causing dental problems. The aim of this research is to determine the management of Dental and Oral Health Care for Mr. A (19 years) with complaints of calculus. The research method used is a case report with the concept of dental and oral health care which consists of a process of assessment,diagnosis, planning, implementation and evaluation for the client Mr. A. The results of the action process provided through dental and oral health care for Mr. A show that there are 3 basic human needs have been achieved and 1 basic human need has only been partially achieved, so the 8 basic human needs of client T,n A have not been fully achieved. because the patient has not made a referral.